Chromosome-level genome assembly of Cyperus iria, an aggressive weed of rice - Siyu Yang; Qingyi Cao; Zexin Wen; Aoxue Wang; Shiyao Shi; Zhuoying Liang; Shuying Li; Wenjun Gui; Jinwen Zhu (Scientific Data)
Abstract Cyperus iria is an aggressive weed of rice throughout the world. Until now, the reference genome of C. iria has not been published. Here, we completed the chromosome-level genome assembly of C. iria based on Illumina, PacBio and Hi-C reads. The assembled genome size of C. iria was 479.08 Mb with a contig N50 of 7.02 Mb. 68 pseudochromosomes were produced using Hi-C scaffolding, accounting for 99.65% of the assembled genome. The number of predicted protein-coding genes is 47,395, of which 93.26% were annotated, and 37.69% repetitive sequences were identified. Our study provided a valuable genomic resource for the molecular biology research and the management of C. iria.